DESIGN, ANALYSIS AND MANUFACTURING OF GO-KART CHASSIS - Prof. S.T. JAGTAP; PRATHAMESH R.CHAVAN (International Journal of Innovations in Engineering Research and Technology, 2021)
This report aims to model, simulate, perform the static and dynamic analysis and fabrication of a go kart chassis consisting of Circular beams. Modelling, simulations are performed using modelling software i.e. PTC CREO 2.0 and analysis on ANSYS V14.5. The maximum deflection is determined by performing dynamic analysis.The chassis is designed such that it requires less material and as well as it is strong enough to withstand the various impacts on it. Strength and light weight were our basic consideration throughout the design of the chassis of the kart. Hence, AISI1018was selected as an appropriate material for design which is a medium carbon steel with properties such aslight weight, high tensile strength, high machinability, better weldability, etc.